ONLINE SHOP LOYALTY TO SUPPLIERS POST COVID-19 IN INDONESIA: DOES EDUCATION LEVEL MATTER? - Yudiantoro, Deny; Setiawan, Didik (UNIVERSITAS NEGERI SURABAYA, 2024)
The Covid-19 pandemic has dealt a severe blow to the world of business and industry. The post-pandemic distribution flow of goods is certainly a complicated problem that needs further research. This research aims to analyze the level of online shop loyalty to suppliers after COVID-19 in Indonesia. The relationship between online stores and suppliers has not been reviewed much in previous research, especially in the current era of digitalization. Judging from existing data, the business run by online stores is currently huge, with an annual transaction value of around 894 trillion. The value of this business contributes 72% to the total Fast-moving Consumer Goods (FMCG) Retail Industry business in Indonesia. This research aims to describe the relationship between online stores and suppliers in terms of their level of loyalty in the business-to-business (B2B) industry. This research also seeks to analyze respondents' answers related to loyalty indicators. The method used in this research is a descriptive analysis method to map the perceptions and opinions of online stores towards suppliers in Indonesia after COVID-19. Next, the Top Two Box method was used to assess the level of loyalty, while the respondent profiles were analyzed using cross-tabulation analysis. The respondents in this study were 550 online shop owners, and the sampling technique used was Proportionate Stratified Random Sampling through a questionnaire distributed online. The research results show that the quality of retail service, trust, commitment, and satisfaction of online stores towards suppliers is relatively good. Meanwhile, product quality and website quality need to be improved. Around 76.4% of online stores are loyal to their suppliers, while the remaining 23.6% prove to be disloyal. The results of this research are useful for supplier companies to establish business-to-business relationships with online stores in Indonesia post-COVID-19 in order to create develop and maintain loyalty from online store partners.